Manajemen Pemeliharaan Kuda di Desa Gantarang, Kabupaten Jeneponto: Horse Farming Management in Gantarang Village, Jeneponto Regency - Ayu Lestari; Handayani Indah Susanti; Suci Ananda; Rusny Rusny (Universitas Islam Negeri Alauddin Makassar, 2023)
The development of horse farms in Gantarang Village has not been in line with the high utilization of horse livestock, so it is necessary to evaluate the management of horse farm maintenance in the area. The research was conducted in September 2022 in Gantarang Village, Kelara District, Jeneponto Regency. The object of this study were horse breeders in Gantarang Village, with 30 respondents. Respondents were selected purposively (purposive sampling) and then interviewed. The results showed that the majority of horse breeders in Gantarang Village raised 1-3 horses (60%). As many as 67% of respondents are private owners of the horses they keep. Horse rearing in Gantarang Village uses an intensive (50%) and semi-intensive (50%) system. The frequency of feeding 3 times was carried out by 67% of breeders and was carried out in the morning, afternoon and evening. All breeders (100%) who raise traditional horses in Gantarang Village only use forages, namely grass and straw. Horse farming in Gantarang Village is still traditional with a low number of horse owners. The provision of forage is carried out using the cut and carry method, namely taking feed from another location as far as 1-2 km from the location of the stable and bringing it to the stable or where the horses are grazed. Research on horse farming, especially in Jeneponto Regency, must be continued as one of the efforts to improve the community's economy, preserve culture, germplasm and the environment, develop livestock quality and health, and sustain horse production in the future.